A Rare Case Of Acanthamoeba Endophthalmitis Following Cataract Surgery - Vishal Raval; Rushil Saxena; Joveeta Joseph; Savitri Sharma; Raja Narayanan (Delhi Journal of Ophthalmology)
Acanthamoeba are ubiquitous microorganisms and are considered opportunistic pathogens in humans. Acanthamoeba infection involving the vitreous, retina or choroid is uncommon and is mostly seen following corneal infections or corneal transplant surgeries. (1,2) We present a rare case of post-operative endophthalmitis due to Acanthamoeba in a 30-year old gentleman who underwent cataract surgery in his left eye. The initial routine microscopy and culture reports were negative for bacteria and fungus, and inspite of empirical treatment for endophthamitis, the patient's ocular condition worsened. Following multiple vitrectomy surgery and repeated negative culture as well as polymerase chain reaction (PCR) for bacteria, virus and fungi, PCR for Acanthamoeba species was reported positive. On starting the patient on intravitreal and topical voriconazole along with oral ketoconazole the patient's eye condition improved with moderate recovery of visual acuity. To the best of our knowledge, this is the first case reported of Acanthamoeba endophthalmitis following cataract surgery.